Strategies for Appropriate Patient-centered Care to Decrease the Nationwide Cost of Cancers in Korea - Bae, Jong-Myon (J Prev Med Public Health, 2017)
In terms of years of life lost to premature mortality, cancer imposes the highest burden in Korea. In order to reduce the burden of cancer, the Korean government has implemented cancer control programs aiming to reduce cancer incidence, to increase survival rates, and to decrease cancer mortality. However, these programs may paradoxically increase the cost burden. For examples, a cancer screening program for early detection could bring about over-diagnosis and over-treatment, and supplying medical services in a paternalistic manner could lead to defensive medicine or futile care. As a practical measure to reduce the cost burden of cancer, appropriate cancer care should be established. Ensuring appropriateness requires patient-doctor communication to ensure that utility values are shared and that autonomous decisions are made regarding medical services. Thus, strategies for reducing the cost burden of cancer through ensuring appropriate patient-centered care include introducing value-based medicine, conducting cost-utility studies, and developing patient decision aids.